Model of environmental management due to coal mining on the Separi River in Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan Province - Efendi, Nur; Barlian, Eri; Syah, Nur Hasan; Dewata, Indang; Arif, Dian Adhetya; Umar, Iswandi (Brawijaya University, 2024)
Coal mining has a significant impact on reducing river water quality. The decline in river water quality causes problems for human life and the environment. Therefore, this research aimed to evaluate river water quality and develop strategies for improving river water quality due to open pit coal mining activities in Tenggarong Seberang District and develop environmental improvement strategies. Several chemical parameters, including pH, TSS, Fe, and Mn, were observed through laboratory tests to determine water quality in the Separi River used in coal mining. The next step was determining environmental improvement strategies using the ISM approach. Twenty stakeholders from related agencies and institutions using FGD were involved in developing a policy strategy. The results of the analysis showed that there has been a decrease in river water quality standards due to mining activities in the research area, and the quality is still below the standard quality. Therefore, two significant strategies must be a priority for the environmental management of the Separi River. First, Conducting an environmental audit of the factors causing the decline in river water quality is necessary. Second, there must be warnings and legal sanctions for negligence in oil spills and oil used from coal mining.